Die periglazial-morphologischen Wirkungen des Eiszeitklimas auf der ganzen Erde:: Beiträge zur Geomorphologie der Klimazonen und Vorzeitklimate IX. - Büdel, Julius (ERDKUNDE, 1953)
The paper deals with the climate of the Würm glacial period which is taken as an example of all former cold periods of the pleistocene epoch. In these periods, while the regions outside the tropics were particularly cold and at the same time drier than at present, the tropical regions were more humid and only moderately colder than today. As a result of this there was a different distribution of the major climatic belts over the earth; the change was most pronounced near the poles and least important near the equator, as is shown in fig. 1. Since these climatic belts of the cold period, with the exception of the equatorial regions proper, differed so markedly from those of today, different morphogenetic processes, producing a different set of landforms, were operating in them. This has long been known so far as the then ice covered zone and the zone of moraines are concerned. The main purpose of this paper is to discuss the glacial landforms in all the other climatic zones. (The term periglacial should only be applied to relief features of the immediate margins of the former ice sheets). Where powerful processes were at work in the glacial periods, and only weak processes in the holocene, these glacial landforms are still the characteristic features of the relief, but where the glacial processes were weak and the holocene strong, the glacial landforms have been transformed into those resulting from present day climatic conditions. The regular grading of this relationship is illustrated by fig. 3. Finally the paper discusses the question whether there was just one Würm glacial period, or whether this period is to be subdivided (W I, W II, W III). The case for a single uninterrupted Würm glaciation is put forward; contrary opinions are discussed and it is shown that the existing difficulties are only apparent and can easily be solved by a simple change in the nomenclature. The new picture of the climatic development of the later pleistocene which thus results is shown in fig. 2 and 4.